Estudo comparativo de métodos de detecção de lesões precursoras de carcinoma espinocelular anal pós-tratamento de condilomas acuminados anais. - Nadal, Luis Roberto Manzione [UNIFESP] (2018)
Objective: To evaluate the presence of remaining anal canal and margin subclinical HPVinduced lesions with cytology, anal colposcopy and HPV genotyping by PCR in newly treated individuals with no macroscopically visible HPVinduced lesions, and to verify the influence of the immunological status on the results. Methods: A prospective study of 79 male patients over 18 years of age consecutively included after 30 days of anal warts treatment by topical medication or surgery, with no visible macroscopic lesions. During a single appointment, they were submitted to the collection of two brush samples for cytopathological study of the anal canal and another for PCR, then to anal colposcopy with 3% acetic acid in the margin and in the anal canal. The individuals were grouped according to HIV infection status: I) HIVnegative; II) HIVpositive with a CD4 T lymphocyte count above 350 cells/mm3; III) HIVpositive CD4 Tlymphocyte count below 350 cells/mm 3. After that we regrouped: A) satisfactory CD4 T lymphocytes (Groups I + II vs Group III), B) HIV seropositivity (Groups I vs Groups II + III) and C) presence of detectable HIV viral load. We compared the presence of oncogenic types of HPV detected by PCR with the finding of high grade cytology lesions (HSIL) and acetowhite lesions at colposcopy and biopsy guided by it, within and between groups. Results: There were no differences in cytological, colposcopic or histopathological findings between groups. HPV DNA was isolated in 69 (92%) of the 75 subjects from whom samples were analyzed for this test. The most frequent HPV type was 6, followed by 16. The presence of HIV infection was associated with a higher number of oncogenic HPV types (p=0.038). All six patients with negative PCR had negative anal colposcopy and cytology. The only two cases of NIAA with histological confirmation were positive for anal colposcopy and had oncogenic HPV types on PCR. Conclusion: The association of the results of cytopathology, anal colposcopy and genotyping of the HPV virus increased the diagnostic sensitivity of HPVinduced lesions, with PCR genotyping with findings corresponding to those of the anal colpocytological examination. In this study, the degree of immunodeficiency shown by the T CD4 count was not associated with the increase in remnant HPVinduced anal lesions.